hUC-MSCs Attenuate Acute Graft-Versus-Host Disease through Chi3l1 Repression of Th17 Differentiation - Weijiang Liu; Fulin Yuan; Haitao Bai; Yuanlin Liu; Xue Li; Yang Wang; Yi Zhang (Stem Cells International, 2022)
Mesenchymal stem cells (MSCs) have already demonstrated definitive evidence of their clinical benefits in acute graft-versus-host disease (aGvHD) and other inflammatory diseases. However, the comprehensive mechanism of MSCs’ immunomodulation properties has not been elucidated. To reveal their potential immunosuppressive molecules, we used RNA sequencing to analyze gene expression in different tissue-derived MSCs, including human bone marrow, umbilical cord, amniotic membrane, and placenta, and found that chitinase-3-like protein 1 (Chi3l1) was highly expressed in human umbilical cord mesenchymal stem cells (hUC-MSCs). We found that hUC-MSCs treated with interferon-gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-α) exhibited increased expression of Chi3l1 and concurrently repressed T-helper 17 cell (Th17) differentiation through inhibition of signal transducer and activator of transcription 3 (STAT3) activation. Furthermore, Chi3l1 knockdown hUC-MSCs exhibited impaired therapeutic efficacy in aGvHD mice with an increased inflammatory response by promoting Th17 cell differentiation, including an increase in IL-17A in the spleen, intestine, and serum. Collectively, these results reveal a new immunosuppressive molecule, Chi3l1, in hUC-MSCs in the treatment of aGvHD that regulates Th17 differentiation and inhibits STAT3 activation. These novel insights into the mechanisms of hUC-MSC immunoregulation may lead to the consistent production of hUC-MSCs with strong immunosuppressive functions and thus improved clinical utility.